2013
DOI: 10.6110/kjacr.2013.25.6.346
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Air-Conditioning and Refrigeration Research : A Review of Papers Published in the Korean Journal of Air-Conditioning and Refrigeration Engineering in 2012

Abstract: This article reviews the papers published in the Korean Journal of Air-Conditioning and Refrigeration Engineering during 2012. It is intended to understand the status of current research in the areas of heating, cooling, ventilation, sanitation, and indoor environments of buildings and plant facilities. The conclusions are as follows: (1) The research works on thermal and fluid engineering have been reviewed as groups of fluid machinery, pipes and valves, fuel cells and power plants, ground-coupled heat pumps,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 113 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Ha 15 investigated the cycle performance under various refrigerant charge amounts and the cycle characteristics according to the mass flow distribution in a multiple heat pump using R22. Chung et al 16 compared the performance of an air conditioner which uses R410A and R22 at various refrigerant charge amounts and outdoor temperature. Li and Braun 17 presented a general methodology for detecting and diagnosing multiple simultaneous faults in vapor compression air conditioners using low-cost measuring elements.…”
Section: Introductionmentioning
confidence: 99%
“…Ha 15 investigated the cycle performance under various refrigerant charge amounts and the cycle characteristics according to the mass flow distribution in a multiple heat pump using R22. Chung et al 16 compared the performance of an air conditioner which uses R410A and R22 at various refrigerant charge amounts and outdoor temperature. Li and Braun 17 presented a general methodology for detecting and diagnosing multiple simultaneous faults in vapor compression air conditioners using low-cost measuring elements.…”
Section: Introductionmentioning
confidence: 99%
“…Previous experimental and theoretical studies showed that strati¯cation enhancement technology, which increases the temperature di®erence between the top and bottom of the storage tank, results in the higher collection e±ciency and higher thermal exergy. [2][3][4][5][6] Various di®users and distributors are widely acknowledged as the mechanisms maximizing the strati¯cation performance. However, it is not considered to be a good strategy to adopt such di®user and distributor in the forced circulation system due to insu±cient strati¯cation performance.…”
Section: Introductionmentioning
confidence: 99%